Personality traits orientation of University Kebangsaan Malaysia (UKM) and UKM - University Duisburg-Essen (UDE) engineering students - Mastor K.A.; Sulehan J.; Mustafa J.; Pawanteh L.; Basri H.; Abdullah S.; Mokthtar A.; Ghani Z.A.; Axel H. (2024)
Indexed by SCOPUS/WOS